3D biomaterial models of human brain disease - Kajtez, Janko; Nilsson, Fredrik; Fiorenzano, Alessandro; Parmar, Malin; Emnéus, Jenny (Neurochemistry international, 2021)
Inherent limitations of the traditional approaches to study brain function and disease, such as rodent models and 2D cell culture platforms, have led to the development of 3D in vitro cell culture systems. These systems, products of multidisciplinary efforts encompassing stem cell biology, materials engineering, and biofabrication, have quickly shown great potential to mimic biochemical composition, structural properties, and cellular morphology and diversity found in the native brain tissue. Crucial to these developments have been the advancements in stem cell technology and cell reprogramming protocols that allow reproducible generation of human subtype-specific neurons and glia in laboratory conditions. At the same time, biomaterials have been designed to provide cells in 3D with a microenvironment that mimics functional and structural aspects of the native extracellular matrix with increasing fidelity. In this article, we review the use of biomaterials in 3D in vitro models of neurological disorders with focus on hydrogel technology and with biochemical composition and physical properties of the in vivo environment as reference. •Extracellular matrix plays a crucial role in healthy and diseased brain.•Biochemical and mechanical properties of the native brain extracellular matrix are unique.•Biomaterials, in particular hydrogels, mimic aspects of brain extracellular matrix in vitro.•Natural and synthetic hydrogels allow generation of 3D in vitro models of brain disease.•Hybrid bioengineering technologies are developed to enhance 3D hydrogel cultures.